Pelatihan Penyusunan Proposal Dan Pelaporan Penelitian Tindakan Kelas (PTK) Bagi Para Guru Madrasah Aliyah Negeri Kota Bengkulu - Riswanto Riswanto; Deko Rio Putra; Maya Linda Sari; Karin Zahra (Yayasan Darussalam Bengkulu, 2026)
Classroom Action Research (CAR) is an important tool for teachers to improve the quality of learning and professionalism. However, teachers at the State Islamic Senior High School (Madrasah Aliyah) in Bengkulu City still face obstacles in designing proposals and preparing CAR reports correctly and in a structured manner. Therefore, this training activity was held to strengthen teacher capacity through an understanding of basic CAR concepts, proposal and report writing strategies, and hands-on practice in creating CAR documents. The activity was carried out in stages, starting from identifying classroom problems, formulating objectives, selecting a methodological approach, and preparing the final report. The results of the activity showed that teachers experienced increased knowledge and skills in preparing CAR proposals and reports, and demonstrated a strong commitment to implementing the training outcomes in the learning process. This training also encouraged a culture of research among madrasah teachers and facilitated the fulfillment of promotion requirements. For sustainable impact, it is recommended that such training be conducted periodically with more intensive field mentoring.